2003
DOI: 10.1093/aje/kwg210
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight as a Risk Factor for Childhood Leukemia: A Meta-Analysis of 18 Epidemiologic Studies

Abstract: Evidence has emerged that childhood leukemia is initiated in utero. High birth weight is one of the few birth-related factors that has been associated with childhood leukemia, albeit not consistently. The authors conducted a meta-analysis of studies of the association between birth weight and childhood leukemia risk. Study-specific odds ratios for leukemia were calculated, using a cutoff at 4,000 g of birth weight. The authors also evaluated whether the association between birth weight and leukemia followed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 62 publications
7
120
2
2
Order By: Relevance
“…62,81 McCormack et al found a significant positive association between birth weight and cancer in the lymphatic and haematopoietic tissue in adult persons, and a similar tendency was seen for multiple myeloma and Non-Hodgkin lymphoma. A metaanalysis of more than 10 000 children concluded with an increased risk of acute lymphoblastic leukaemia for those with a birth weight of more than 4000 g compared with weight less than 4000 g. 85 These results have been confirmed in a recent Nordic study. 86 Neither McCormack et al 62 nor Ahlgren et al 81 could find any association between birth weight and cancer in the brain or the nervous system in adult persons.…”
Section: Birth Weightmentioning
confidence: 82%
“…62,81 McCormack et al found a significant positive association between birth weight and cancer in the lymphatic and haematopoietic tissue in adult persons, and a similar tendency was seen for multiple myeloma and Non-Hodgkin lymphoma. A metaanalysis of more than 10 000 children concluded with an increased risk of acute lymphoblastic leukaemia for those with a birth weight of more than 4000 g compared with weight less than 4000 g. 85 These results have been confirmed in a recent Nordic study. 86 Neither McCormack et al 62 nor Ahlgren et al 81 could find any association between birth weight and cancer in the brain or the nervous system in adult persons.…”
Section: Birth Weightmentioning
confidence: 82%
“…A recent meta-analysis of 18 studies from the 1940s onward found higher risk of ALL with birth weight of over 4000 g (pooled odds ratio of 1.26, 95% confidence interval 1.17 -1.37) (Hjalgrim et al, 2003). In addition, risk increased 14% with each 1000 g increase in birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…25 It has been hypothesized that prenatal biologic processes are important for several other cancers as well, [30][31][32] but to our knowledge it has to date only been convincingly demonstrated for the development of childhood leukemia. 33 Testing this hypothesis for adult cancers with sufficient power requires very large cohorts with long follow-up periods. To our knowledge, only 2 studies published to date have addressed the significance of birth weight in the development of cancer in general.…”
mentioning
confidence: 99%